Reducing information asymmetry with ICT: A critical review of loan price and quantity effects in Africa. Issue 2 (7th March 2019) - Asongu, Simplice; le Roux, Sara; Nwachukwu, Jacinta; Pyke, Chris
Abstract : Purpose: The purpose of this paper is to investigate loan price and quantity effects of information sharing offices with information and communication technology (ICT), in a panel of 162 banks consisting of 42 African countries for the period 2001–2011. Design/methodology/approach: The empirical evidence is based on a panel of 162 banks in 42 African countries for the period 2001–2011. Misspecification errors associated with endogenous variables and unobserved heterogeneity in financial access are addressed with generalized method of moments and instrumental quantile regressions. Findings: The findings uncover several major themes. First, ICT when integrated with the role of public credit registries significantly lowered the price of loans and raised the quantity of loans. Second, while the net effects from the interaction of ICT with private credit bureaus (PCBs) do not improve financial access, the corresponding marginal effects show that ICT could complement the characteristics of PCBs to reduce loan prices and increase loan quantity, but only when certain thresholds of ICT are attained. The authors compute and discuss the policy implications of these ICT thresholds for banks with low, intermediate and high levels of financial access. Originality/value: This is one of the few studies to assess how the growing ICT can be leveraged in order to reduce information asymmetry in the banking industry with the ultimate aim of improving financial access in a continent where lack of access to finance is a critical policy syndrome.